Pengelolaan Supervisi Klinis Di SdAl Islam 2 Jamsaren Surakarta - Sumadi, Sumadi; , Prof. Dr. Markhamah, M. Hum; , Dr. Ahmad Fathoni, M. Pd (2017)
The objectives of the research are to describe: 1) the implementation of clinical supervision; 2) results and follow-up of the clinical supervision; and 3) the supporting and inhibiting factors of the clinical supervision implementation at SD Al Islam 2 Jamsaren of Surakarta. The type of the research is a qualitative research. The design of the researh is naturalistic design. The research was undertaken at SD Al Islam 2 Jamsaren of Surakarta. The object of the research was the principal's leadership at SMP Negeri 2 Kaliwungu Kendal. The data collecting method is done using observation, i -depth interview, and document techniques. The data analysis is done using interactive model consists of three main components, namely data reduction, data display, and verification. The data validation is done using continuous observation, data triangulation, and member check techniques. Based on the analysis the research concludes that: 1) the implementation of clinical supervision at SD Al Islam 2 Jamsaren of Surakarta was done in three stages, namely initial interview, observation, and evaluation or feedback. The principal, during the implementation, observed the teaching process undertaken by the teachers using observation instrument sheet developed together in accordance to the shared contract. Using such a process, the teachers' competence in teaching using curriculum of 2013 improved; 2) The results and follow up of the clinical supervision at SD Al Islam 2 Jamsaren of Surakarta is that teachers able to improve their teaching practices and aware of their weaknesses in teaching; and 3) the supporting factors of the clinical supervision at SD Al Islam 2 Jamsaren of Surakarta cover the teachers' availability to accept the principal's guidance, and the relative relationship among teachers, and between teacher and the principal. The inhibiting factors of the clinical supervision at SD Al Islam 2 Jamsaren of Surakarta cover yhe principal's business with routine duty so that she should spend the available time to implement the clinical supervision.